(3eaghe GdOhdI YfO CQSWh h ehbag GdfbOj ef GdCfXeI GdSjGSjI GdSGHbI (B= s Aristotle`s concept of the state and his critical attitude of the previous political systems - (3YGFTI YHOGdSdGe RcQj YHOGddg GdeMLhHs; (3eUWai MSf GdfTGQ (B: s ((3GdbGgQI (B: s (3YGFTI YHOGdSdGe RcQj YHOGddg GdeMLhH (B: s, 2013)
(3Ef gPG GdHMK JJVef ehVhYB HYfhGf (B( (3eaghe GdOhdI YfO CQSWh h ehbag GdfbOj ef GdCfXeI GdSjGSjI GdSGHbI (B) . (3h gh eNUU JMOjOB dOQGSI eaghe GdOhdI YfO CQSWh (B: (3Ke Cge GdGfJbGOGJ GdJj hLggG CQSWh Edi CSJGPg CadGWhf HNUhU GdTjhYjI aj GdOhdI (B: (3Ke jJWQb Edi Cge GdOSGJjQ GdJj JfGhdgG CQSWh HGdJMdjd h GdOQGSI (B. (3dPG abO bSeJ GdOQGSI Edi NeSI aUhd (B: (3h bSeJ gPg GdaUhd Edi eHGMK YOI (B: (3h PjdJ gPg GdOQGSI HNGJeI JVefJ Cge GdfJGFL GdJj JhUdJ EdjgG gPg GdOQGSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdadSaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdOhdIs; (3GdSjGSIs; (3GdfXGes